Mutagenesis Screening of a Producing L-Malic Acid Aspergillus niger Strain and Optimization of Fermentation Medium - Shutong LIU; Bingbing SHI; Yiyang TAN; Chengwei LI; Caixia WEI; Depei WANG; Xianli XUE (Shipin gongye ke-ji, 2024)
In order to screen a strain of Aspergillus niger with high L-malic acid production ability, a wild-type strain was mutagenized into a strain with high L-malic acid production ability by iterative mutagenesis with UV mutagenesis and high concentration of actinomycinone, and the composition of its seed or fermentation medium was optimised. It showed that the optimal glucose concentration of the seed medium was 60 g/L, the optimal nitrogen source was (NH4)2SO4 with 4.95 g/L, and the optimal rotational speed for the formation of A. niger spheres was 220 r/min. The optimal concentration of glucose and (NH4)2SO4 of the fermentation medium were 180 g/L and 4.95 g/L, respectively. CuSO4·5H2O was the best trace element for the production of malic acid, with the optimal addition amount of 0.065 g/L. The optimized medium was more conducive to the synthesis of L-malic acid through the optimization of the one-way experiments. The results presented that the production of L-malic acid at 96 h reached 18.15 g/L , which was significantly improved by 245%, and the percentage of L-malic acid in the total acid reached 71.69%. This study lays the foundation for the industrial production of L-malic acid.